Abscisic Acid as an Emerging Modulator of the Responses of Plants to Low Oxygen Conditions - González-Guzmán, Miguel; Gómez-Cadenas, Aurelio; Arbona, Vicent (Frontiers in Plant Science, 2021)
Different environmental and developmental cues involve low oxygen conditions, particularly those associated to abiotic stress conditions. It is widely accepted that plant responses to low oxygen conditions are mainly regulated by ethylene (ET). However, interaction with other hormonal signaling pathways as gibberellins (GAs), auxin (IAA) or nitric oxide (NO) has been well documented. In this network of interactions, abscisic acid (ABA) has always been present and regarded to as a negative regulator of the development of morphological adaptations to soil flooding: hyponastic growth, adventitious root emergence or formation of secondary aerenchyma in different plant species. However, recent evidence points towards a positive role of this plant hormone on the modulation of plant responses to hypoxia and, more importantly, on the ability to recover during the post-hypoxic period. In this work, the involvement of ABA as an emerging regulator of plant responses to low oxygen conditions alone or in interaction with other hormones is reviewed and discussed.